Prevalence of Orthopaedic Knee Scooter-Related Injury: Risk Factor Analysis and Patient Safety Perceptions in a Prospective Cohort. Issue 4 (November 2022) - Walsh, John P.; Hsiao, Mark S.; Rosevear, Landon; McDermott, Ryland; Gupta, Shivali; Watson, Troy S.
Category: Other; Trauma Introduction/Purpose: There is a paucity of research investigating the harms associated with the orthopaedic knee scooter (OKS) and patient safety perceptions. This prospective study aimed to define the prevalence of OKS-related injuries, identify patient risk factors and describe the patient perceptions of OKS safety. Methods: This single-surgeon prospective study recruited a cohort of 134 consecutive patients undergoing surgery at a community-based orthopaedic clinic from 6/2020 to 4/2021. Our primary outcome informed an a priori power analysis. Standardized data collection protocol included three forms that patients completed. The prevalence of OKS-related injury, patient risk factors, and patient perceptions were analyzed. Alpha values of P <0.05 were considered statistically significant, and a 95% confidence interval was reported (95CI). Results: There were 118 (88%) patients eligible for analysis. The prevalence of patient falls was 37.3% (44/118), and the prevalence of patient injury was 15.3% (18/118). A sedentary lifestyle was a significant risk factor (P=0.001) for injury, with a relative risk of 3.32 (1.47- 7.46 95CI) and an absolute risk difference of 26%. Age, height, weight, diabetes was not found to be risk factors for injury. Patient perception of OKS safety at study enrollment (P=0.049) and study exit (P=0.004) were significantly lower for injured patients. Conclusion: Despite a high prevalence of patient falls, there is a low absolute risk of injury. Sedentary patients are at increased risk of OKS-related injury. Patients with a history of injury perceive OKSs to be less safe and are less likely to use an OKS in the future but are not less likely to recommend an OKS to a friend. Future studies should verify prevalence data in multiple settings and assess the effectiveness of patient education or surgeon screening measures in reducing OKS-related injury.